2018
DOI: 10.13057/biodiv/d190131
|View full text |Cite
|
Sign up to set email alerts
|

The ethnobotanical study of edible and medicinal plants in the home garden of Batak Karo sub-ethnic in North Sumatra, Indonesia

Abstract: Silalahi M, Nisyawati. 2018. The ethnobotanical study of edible and medicinal plants in the home garden of Batak Karo subethnic in North Sumatra, Indonesia. Biodiversitas 19: 229-238. The cultivation of plants in home gardens for self-sufficiency is a long tradition in Karo District, but the documentation of local knowledge about edible and medicinal plants in home gardens in Karo District is limited. This study aimed to (i) document the uses of the edible and medicinal plants in home gardens; (ii) to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 32 publications
1
40
0
9
Order By: Relevance
“…In Bali, for example, there is loloh, a traditional herbal drink for treatment and health care (Sujarwo et al 2015). Public awareness about medicinal plants has also increased through cultivation of crops and medicinal plants in garden, as commonly practiced by the Batak Karo community (Silalahi and Nisyawati 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Bali, for example, there is loloh, a traditional herbal drink for treatment and health care (Sujarwo et al 2015). Public awareness about medicinal plants has also increased through cultivation of crops and medicinal plants in garden, as commonly practiced by the Batak Karo community (Silalahi and Nisyawati 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These species were used to cure diseases and to maintain fitness. The number of species recorded in this study is fewer than that in Batak Karo with is 85 species (Silalahi and Nisyawati 2018) and is fewer than that in Bali in which 51 species belong to 32 families are commonly used as loloh, traditional herbal drinks to prevent and to cure diseases (Sujarwo et al 2015). This number is also fewer than that in Bukit Turgo Yogyakarta with 69 species of 36 families (Maizer et al 2016).…”
Section: Resultsmentioning
confidence: 59%
“…For instance, research about medicinal plants in Turgo, Sleman, Yogyakarta revealed 69 species from 36 families with Zingiberaceae, Asteraceae and Euphorbiaceae alone each consisted of 6 species (Maizer et al 2016). In addition, ethnobotanical research about food and medicine in the gardens of Batak Karo people in North Sumatra was also reported by Silalahi and Nisyawati (2018).…”
Section: Introductionmentioning
confidence: 97%
“…[3] In Indonesia, boiled leaves of E. debile has been used to overcome kidney stones. [4] Recently, cytotoxicity and antimicrobial studies revealed that the n-hexane-, ethyl acetate-and n-butanol extract of E. debile aerial stems exhibited quite potent activity in brine shrimp lethality bioassay. [1] Moreover, results of a preliminary study indicated that the chloroform-soluble extract of E. debile exhibited potential cytotoxicity against the brine shrimp nauplii and antioxidative properties in terms of DPPH radical scavenging, total antioxidant capacity and total phenolics content.…”
Section: Introductionmentioning
confidence: 99%